1998
DOI: 10.1175/1520-0477(1998)079<1883:togire>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Operational GOES Infrared Rainfall Estimation Technique

Abstract: This paper presents a description, sensitivity analyses, sample results, validation, and the recent progress done on the development of a new satellite rainfall estimation technique in the National Environmental Satellite Data and Information Service (NESDIS) at the National Oceanic and Atmospheric Administration (NO A A). The technique, called the auto-estimator, runs in real time for applications to flash flood forecasting, numerical modeling, and operational hydrol-ogy. The auto-estimator uses the Geoestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
211
0
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(230 citation statements)
references
References 13 publications
10
211
0
9
Order By: Relevance
“…The different techniques using visible and infrared spectra enable analyzing only the cloud tops (brightness and temperature) and thus are a limiting factor for precipitation estimates [24]. References [25,26] found that techniques using infrared and passive microwave radiation are not very effective for estimate precipitation in NEB, in view of the predominance of shallow clouds with relatively warm tops in this region.…”
Section: Advances In Meteorologymentioning
confidence: 99%
“…The different techniques using visible and infrared spectra enable analyzing only the cloud tops (brightness and temperature) and thus are a limiting factor for precipitation estimates [24]. References [25,26] found that techniques using infrared and passive microwave radiation are not very effective for estimate precipitation in NEB, in view of the predominance of shallow clouds with relatively warm tops in this region.…”
Section: Advances In Meteorologymentioning
confidence: 99%
“…Pure IR techniques are also still used in operational configuration, though they require calibration by independent instruments. Vicente et al (1998) use the IR channels of the Geostationary Operational Environmental Satellite (GOES-8/9) to compute real-time precipitation amounts based on a power law algorithm. The regression is derived from a statistical analysis between surface instantaneous radar rainfall estimates and satellite IR cloud top temperatures collocated in time and space.…”
Section: Discussionmentioning
confidence: 99%
“…Barrett & Michell (1991) give a clear idea of the problem in the Mediterranean basin. Flash flood monitoring in the US, a crucial issue for the national weather prediction system, is becoming operational (Scofield & Naimeng, 1994;Vicente & Scofield, 1996;Vicente et al, 1998). Applications to Italy's precipitation systems have been attempted on several occasions over various time scales and for different precipitation systems.…”
Section: Introductionmentioning
confidence: 99%
“…3a. We also performed data conversion from MTSAT TBB to rainfall intensity (Rm) through a non-linear regression equation that expressed their relationship (Vicente et al 1998). We investigated the relationship between the TBB11 of the classified cloud types and the rain gauge measurements.…”
Section: Multifunctional Transport Satellites (Mtsat)mentioning
confidence: 99%